Larvicidal Activity of A Mixture of Cashew Nut Shell Liquid and Water-Soluble Extract of Soap Nut Fruit (Sapindus rarak DC.) Against 3rd Instar Larvae of Aedes aegypti - Glory Resia Raraswati; Sudarsono Sudarsono; Budi Mulyaningsih (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2014)
Cashew Nut Shell Liquid (CNSL) which has been known as a waste of processing cashew fruits which is contain phenolic compounds have activity as larvicides. Cashew nut shell liquid is not soluble in the water where the larvae grow. Cashew nut shell liquid mixed with water-soluble extract of soapnut fruit which serves as a natural surfactant that can emulsify oil in water. The test subjects were larvae of Aedes aegypti third instar. Test subjects were divided into treatment group and control group. In the treatment group, test subjects were the mixture of CNSL and Ethylacetat Soluble Extract (ESE) in tap water. The Larvae mortality observations were done 24 hours after the treatment. LC50 and LC90 as final test data were analyzed using probit analysis. Extract constituents of CNSL and Water Soluble Extract of SoapNut fruit (WSEoSN) were investigated using Thin Layer Chromatography (TLC) method. The effect of CNSL as larvicides against third instar larvae of Ae. aegypti with were LC50 of 14,12 ppm, while the LC90 of 24,85 ppm.